The synthesis and characterization of 1 1 1 1 type diluted ferromagnetic semiconductor (La1−xCax)(Zn1−xMnx)AsO. (17th December 2015) - Ding, Cui; Guo, Shengli; Zhao, Yao; Man, Huiyuan; Fu, Licheng; Gu, Yilun; Wang, Zhouyang; Liu, L; Frandsen, B A; Cheung, S; Uemura, Y J; Goko, T; et al.
Abstract: We report the synthesis and characterization of a bulk form diluted magnetic semiconductor, (La1− x Ca x )(Zn1− y Mn y )AsO, with a layered crystal structure isostructural to that of the 1 1 1 1 type Fe-based high-temperature superconductor LaFeAsO and the antiferromagnetic LaMnAsO. With Ca and Mn codoping into LaZnAsO, the ferromagnetic ordering occurs below the Curie temperature   ∼30 K. Taking advantage of the decoupled charge and spin doping, we investigate the influence of carrier concentration on the ferromagnetic ordering state. For a fixed Mn concentration of 10%, increases from 24 K to 30 K when the Ca concentration increases from 5% to 10%. Further increase of Ca concentration reduces both the coercive field and saturation moment. Muon spin relaxation measurements confirm the ferromagnetically ordered state, and clearly demonstrate that (La1− x Ca x )(Zn1− y Mn y )AsO shares a common mechanism for the ferromagnetic exchange interaction with (Ga, Mn)As. Neutron scattering measurements show no structural transition in (La0.90 Ca0.10 )(Zn0.90 Mn0.10 )AsO below 300 K.